The Digital Stressors Scale: Development and Validation of a New Survey Instrument to Measure Digital Stress Perceptions in the Workplace Context - Fischer, Thomas; Reuter, Martin; Riedl, René (Frontiers in Psychology, 2021)
This article reports on the development of an instrument to measure the perceived stress that results from the use and ubiquity of digital technology in the workplace. Based upon a contemporary understanding of stress and a set of stressors that is a substantial update to existing scales, the Digital Stressors Scale (DSS) advances the measurement of digital stress. Initially, 138 items were constructed for the instrument and grouped into a set of 15 digital stressors. Based on a sample of N = 1,998 online questionnaires completed by individuals representative of the US employed population, the scale was refined using exploratory factor analyses (EFA) and PLS-SEM. The resulting and final scale consists of ten stressor categories reflective of one higher-order construct and a total of 50 items. Through a nomological network that includes important outcome variables of digital stress (emotional exhaustion, innovation climate, job satisfaction, user satisfaction) it was then demonstrated that the DSS provides substantial explanatory power, particularly related to emotional exhaustion and user satisfaction. Thus, the DSS constitutes a state-of-the-art self-report instrument to measure the extent of distress appraisal related to digital technologies in the workplace and helps to explain further how and why information and communication technologies can lead to adverse outcomes in individuals, thereby providing the starting point for job related organizational interventions.